Differences in Hemoglobin Levels in Patients with Thalassemia Major and Minor at Sultan Agung Semarang Islamic Hospital - Sari, Sri Mayang; Saptaningtyas, Ragil; Putri, Gela Setya Ayu; Sukeksi, Andri (PROSIDING SEMINAR KESEHATAN MASYARAKAT, 2024)
Background: One of the genetic diseases that is usually detected in children is thalassemia. World Health Organization (WHO) states that thalassemia is the most common hereditary disease in the world and has been recognized as a world health problem. Indonesia is one of the countries in the world's thalassemia belt. Thalassemia major is the most severe clinical condition of thalassemia. Thalassemia minor can also be called a carrier trait and does not show clinical symptoms. Supporting examinations can be carried out with simple laboratory tests, one of which is measuring hemoglobin levels. This study aimed to determine the differences in hemoglobin levels in patients with thalassemia major and thalassemia minor at RSI Sultan Agung Semarang. Method: The type of research used was cross-sectional, with a sample size of 48 people. Hemoglobin level data was obtained from the medical records of Sultan Agung Semarang Islamic Hospital. The data distribution is normal, so the difference test is tested using the independent t-test. Result: The average hemoglobin levels in patients with thalassemia major and thalassemia minor are 5.7 mg/dL and 10.6 mg/dL. The independent t-test shows a significance value of 0.00 (<0.05). Conclusion: There are differences in hemoglobin levels in thalassemia major and thalassemia minor patients at Sultan Agung Semarang Islamic Hospital, although hemoglobin levels in both thalassemia major and minor patients are still below the reference value.